JADWAL SHOLAT HASIL KONVERSI KOREKSIAN DAERAH: ANTARA KEPENTINGAN EFISIENSI DAN AKURASI - Jayusman Jayusman (Program Studi Hukum Keluarga Islam, 2014)
Among people stands prayer schedule. This prayer schedule used as a guide in the implementation of praying five times a day. The prayer schedule among astronomers is usually referred to eternal prayer schedule, or prayer schedule of all time. On the schedule there are usually local corrections. This paper will study further on issues of local corrections. Prayer schedule is accurate if it is the result of calculation based on local corrections.Keywords: prayer schedule, local corrections